Optimization of Bis-anthraquinones Production from Endophytic Fungi Diaporthe sp. GNBP-10 - Oktavia, Listiana; Evana, Evana; Fahardita, Reza; Agusta, Andria (Iraqi Journal of Pharmaceutical Sciences, 2023)
Bis-anthraquinones with a unique molecular backbone, (+)-2,2’-epicytoskyrin A (epi) and (+)-1,1′-bislunatin (bis), was produced by endophytic fungi Diaporthe sp GNBP-10 associated with Gambir plant (Uncaria gambier). Epi and bis possess robust antimicrobial activity toward various pathogens. This study focus on knowing the optimum condition of epi and bis production from Diaporthe sp GNBP-10. A series of culture media with various nutrient compositions was investigated in epi and bis production. The content of epi and bis was determined by measuring the area under the curve from TLC-densitometric (scanner) experiment. The linear regression analysis was then applied to obtain the results. The optimized epi and bis production was observed in liquid media 3 containing potato starch and dextrose with the amount of epi produced is 0.484mg while bis content is 0.163mg. The presence of carbohydrates, whether simple sugar or carbohydrate complex, plays an essential role in the bis-anthraquinones production from Diaphorthe sp culture. The presence of minerals and excessive protein sources did not significantly affect bis-anthraquinones production. Keywords: bis-anthraquinone, Diaporthe sp, culture media, regression, TLC scanner